INDUCED IN VIVO MUTAGENESIS USING COLCHICINE IN HYDROGEN PEROXIDE ON M2 COWPEA, YARDLONG BEAN AND COMMON BEAN - Susrama, I Gede Ketut; Pradnyawathi, Ni Luh Made (International Journal of Biosciences and Biotechnology; Vol 7 No 1 (2019), 2020)
Research on doubling plant chromosome using colchicine has been carried out for years with water as its solvent. In this study, an innovation was carried out by trying to do colchicine treatment in hydrogen peroxide. In this in vivo induced mutagenesis research, colchicine in hydrogen peroxide was administered as mutagen on seeds three species of crops i.e. mutan M2 cowpea, yardlong bean, and common bean by soaking method. The results of this research showed that three times multistep mutant (M3) of cowpea was having mutant characteristics that the shape of its leaflet changed from rhombus to ovate. Besides, both yardlong bean varieties used in this research (BLR and KTR) showed indication of a mutant crop that having compound leaves with more than three leaflets in a stalk. Common bean of PTW variety was not attacked by any aphid but it was attacked by leafminer. Finally, we found “rainbow common bean” from this research.